Electrochemical determination of luteolin using molecularly imprinted poly-carbazole on MoS2/graphene-carbon nanotubes nanocomposite modified electrode. (20th December 2017) - Xu, Bingjie; Zhang, Bihong; Yang, Lite; Zhao, Faqiong; Zeng, Baizhao
Abstract: MoS2 /graphene-carbon nanotubes (MoS2 /GN-CNTs) nanocomposite was prepared by hydrothermal method. The nanocomposite combined the high catalysis of MoS2 with the superior electronic conductivity of GN-CNTs, and exhibited high electrochemical sensitivity towards luteolin. A molecularly imprinted polymer (MIP) film deposited by electropolymerization, based on carbazole monomer and luteolin template, was used to improve the selectivity. Thus the resulting electrochemical sensor MIP/MoS2 /GN-CNTs/GCE showed high performance. Its linear detection range and limit of detection were 0.040–2.0 μM and 9.0 nM (S/N = 3), respectively, while its sensitivity was 381.3 μA μM −1 cm −2 . In addition, 1000-fold K +, Na +, Ca 2+, Mg 2+, NO3 −, Cl −, SO4 2− and CO3 2− 500-fold glucose and mannitol, 250-fold cystein, glycine, lysine, citric acid and oxalic acid, and 100-fold urea, ascorbic acid and dopamine did not interfere with the determination of luteolin. Moreover, 5-fold analogs rutin, catechin and naringenin, and 2-fold kaempferide, quercetin and morin also did not influence on its determination. The sensor was applied to the determination of luteolin in carrot and chrysanthemum tea samples and the results were in good agreement with those obtained through HPLC. Graphical abstract: An electrochemical sensor based on molecularly imprinted poly-carbazole on 3D porous MoS2 /GN-CNTs nanocomposite was constructed; it exhibited high sensitivity and selectivity for luteolin. Highlights: The MoS2 /GN-CNTs nanocomposite combined the conductivity of GN-CNTs with the electrocatalytic activity of MoS2 . Molecularly imprinted poly-carbazole was employed to improve sensor selectivity. The molecularly imprinted polymer film was prepared by voltammetry in acetonitrile solution. The sensor showed high sensitivity (381.3 μA μM −1 cm −2 ) and selectivity.